2017
DOI: 10.1242/dmm.028589
|View full text |Cite
|
Sign up to set email alerts
|

Paneth cell disruption-induced necrotizing enterocolitis requires live bacteria and occurs independent of TLR4 signaling

Abstract: Necrotizing enterocolitis (NEC) remains a leading cause of morbidity and mortality in premature infants. Both human surgical specimens and animal models suggest a potential involvement of Paneth cells in NEC pathogenesis. Paneth cells play critical roles in epithelial homeostasis, innate immunity and host-microbial interactions. Yet, the complex interplay between Paneth cell disruption, epithelial barrier dysfunction and microbial-driven inflammation remains unclear in the immature intestine. In this study, mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(78 citation statements)
references
References 52 publications
2
76
0
Order By: Relevance
“…Treatment with diphtheria toxin induces apoptosis of any cells possessing DTR while sparing all other cells. In this model, treatment with diphtheria toxin followed by Klebsiella pneumoniae exposure also produces intestinal injury that is equivalent to human NEC (14,119). These data provide further evidence that it is a disruption of, and not an absence of Paneth cells that contributes to development of NEC-like injury in the immature small intestine.…”
Section: Paneth Cells and Necrotizing Enterocolitis (Nec)supporting
confidence: 53%
See 2 more Smart Citations
“…Treatment with diphtheria toxin induces apoptosis of any cells possessing DTR while sparing all other cells. In this model, treatment with diphtheria toxin followed by Klebsiella pneumoniae exposure also produces intestinal injury that is equivalent to human NEC (14,119). These data provide further evidence that it is a disruption of, and not an absence of Paneth cells that contributes to development of NEC-like injury in the immature small intestine.…”
Section: Paneth Cells and Necrotizing Enterocolitis (Nec)supporting
confidence: 53%
“…Interestingly, when Paneth cells are disrupted in neonatal rats followed by enteral exposure to E. coli, there is not only an increase in bacterial translocation, but also a development of NEC-like injury to the small intestinal tract (105). In adapting this model to mice, our laboratory and others have shown that selective ablation of Paneth cells followed by enteric gavage of Klebsiella pneumoniae in 14-days old mice results in grossly necrotic intestines (89,(117)(118)(119), an increase in serum inflammatory markers (119), and alterations in the microbiome (14) that are consistent with human NEC. The use of 2-weeks old mice in this model is potentially advantageous as well as they possess a gene expression profile of epithelial cell genes that matches the expression profile seen in preterm human infants during the window when they are most susceptible to develop NEC (18,67).…”
Section: Paneth Cells and Necrotizing Enterocolitis (Nec)mentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were normalized for the amount of protein obtained and maternal serum, placental homogenates, and amniotic fluid samples were quantified for cytokine levels (IL-1β, IL-6, IL-10, KC-GRO TNF, IL-2, IL-4, IL-5, IL-12, and INFγ) using a Meso Scale Discovery technology as previously described. 16 Non-significant cytokines differences are not shown.…”
Section: | Materials and Methodsmentioning
confidence: 99%
“…Although we used a well-accepted model of NEC, the relevance of SIGIRR to Paneth cell ablation (19) and trinitrobenzene sulfonic-acid models (20) of experimental NEC need to be investigated, as these models probe different pathogenic mechanisms underlying NEC.…”
Section: Discussionmentioning
confidence: 99%